A pilot study of ball impact characteristics in varied ball launched directions in soccer instep kick - Inoue, K.; Nunome, H. (ISBS Proceedings Archive (Michigan), 2018)
The purpose of the present study was to identify the characteristics of ball impact foot motion in various ball launched directions. Eighteen trials of soccer instep kicking targeting six areas of the full-size soccer goal at 11 m, were analysed. The collision between the foot and ball was recorded using three ultra-high-speed cameras at 2000 Hz. The foot contact point on the ball and the foot swing direction had a strong correlation with the ball launch direction. It can be interpreted that the foot contact point and swing direction are essential factors to kick the ball towards the targeting direction. Moreover, the roll angle of the foot segment significantly affected the ball launch direction. This result suggested that the roll angle has a role in facing the instep of the foot towards the target direction in order to control the ball launch direction.